Case Report: The effective treatment of patients in advanced no-small cell lung cancer patients with EGFR G719X/S768I/L861Q and acquired MET amplification: A case series and literature review - Zhao, Yun; Su, Cuiyun; Shi, Lina; Luo, Wenqi; Liu, Zhen; Liang, Chuqiao; Wang, Huilin; Ning, Ruiling; Yu, Qitao; Jiang, Wei (Frontiers in Oncology, 2023)
Preclinical cases suggest that EGFR tyrosine kinase inhibitors (TKIs) plus MET TKIs are a potential therapy for non-classical EGFR mutant lung cancers with MET amplification acquired resistance. Herein, we report for the first time the effectiveness of novel combination treatment regimens for patients with EGFR G719X/S768I/L861Q. Until the last follow-up assessment, two patients demonstrated improved survival after they switched to afatinib combined with savolitinib (PFS: 10 months) and furmonertinib combined with crizotinib (PFS: 6 months), respectively, that did not observed increased incidence and severity of adverse events. According to the findings of this study and literature review, various responses were observed from the combined therapy in NSCLC patients who harbored uncommon EGFR mutations and MET amplification. Furthermore, Next generation sequencing (NGS) leads to the discovery of uncommon of EGFR and reveals the co-mutations in NSCLC.